2022
DOI: 10.3390/healthcare11010131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Resistance Training on Body Composition, Hemodynamic Parameters and Exercise Tolerance among Patients with Coronary Artery Disease: A Systematic Review

Abstract: Background: Effectiveness and safety of Resistance Training in treating various Cerebrovascular Disease diagnoses have drawn attention in recent years. Patients suffering with coronary artery disease should be offered individually tailored Resistance Training in their exercise regimen. Resistance Training was developed to help individuals with their functional status, mobility, physical performance, and muscle strength. Objective: The objective of this review was to collect, summarize and present information o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…Our exercise protocol was found to be effective in improving body composition by increasing lean muscle mass and reducing the percentage of fat mass in both exercise groups. In agreement with our findings, a recent systematic review indicated that RT not only could improve body composition but could also improve the haemodynamic parameters and exercise tolerance in patients with CAD ( 31 ). Thus, the RT component in our exercise programme could also promote improvements in VO 2peak via haemodynamic upregulation, leading to increased exercise tolerance.…”
Section: Discussionsupporting
confidence: 93%
“…Our exercise protocol was found to be effective in improving body composition by increasing lean muscle mass and reducing the percentage of fat mass in both exercise groups. In agreement with our findings, a recent systematic review indicated that RT not only could improve body composition but could also improve the haemodynamic parameters and exercise tolerance in patients with CAD ( 31 ). Thus, the RT component in our exercise programme could also promote improvements in VO 2peak via haemodynamic upregulation, leading to increased exercise tolerance.…”
Section: Discussionsupporting
confidence: 93%
“…CAD is a major cardiovascular disease and an important cause of death in developed and developing countries. 24 Because early diagnosis and recognition are essential for the prevention and treatment of the disease, new noninvasive diagnostic methods, including biomarkers, are needed. The basic pathogenesis of CAD is atherosclerosis, 25 which is a complex, persistent and progressive inflammatory disease, characterized by lipid retention and remodeling of the coronary arteries that deliver oxygen and nutrition to the heart tissue, leading to the formation of atherosclerotic plaque and instability.…”
Section: Discussionmentioning
confidence: 99%
“…Core strength training exercises can improve the basic skills of soccer players (Li & Siriphan, 2023). Weight training also has an effect on body composition (Sharma, et al, 2023).…”
Section: Discussionmentioning
confidence: 99%